PERANCANGAN ARTBOOK VISUAL KARAKTER KABA ANGGUN NAN TONGGA - Aulia Rahman; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The purpose of designing the visual character artbook the saga of Anggun Nan Tongga is for  teenagers to know more about the characterizations in the Anggun Nan Tongga story, as well as cultural promotion so that youth participate in loving their own culture. The lack of media information about Kaba Anggun Nan Tongga makes many teenagers currently not aware of Kaba Anggun Nan Tongga, let alone the character of Anggun Nan Tongga itself.This design uses theories, such as illustration theory, print media (books), visual communication design, layout, color, is the theory used in the visual artbook design of Kaba Anggun Nan Tongga characters. Research and Development (R&D), the research method used to produce the artbook, and test the effectiveness of the Kaba Anggun Nan Tongga artbook itself, using SWOT analysis to obtain data obtained in the design of the artbook.The design output is that artbook which is the main media is also accompanied by supporting media to attract people's attention to the lauching process of Kaba Anggun Nan Tongga's artbook, such as x-banners, t-shirts, stickers, posters, and bookmarks. The design output is also in the form of  articles published in the journal DKV FBS UNP.Kata kunci : saga, artbook, character, media